The effectiveness of intrauterine insemination: A matched cohort study. (May 2017) - Scholten, Irma; van Zijl, Maud; Custers, Inge M.; Brandes, Monique; Gianotten, Judith; van der Linden, Paul J.Q.; Hompes, Peter G.A.; van der Veen, Fulco; Mol, Ben W.J.
Abstract: Objective: To study the effectiveness of an intrauterine insemination (IUI) program compared to no treatment in subfertile couples with unexplained subfertility and a poor prognosis on natural conception. Study design: A retrospective matched cohort study in which ongoing pregnancy rates in 72 couples who voluntarily dropped out of treatment with IUI were compared to ongoing pregnancy rates in 144 couples who continued treatment with IUI. Couples with unexplained subfertility, mild male subfertility or cervical factor subfertility who started treatment with IUI between January 2000 and December 2008 were included. Couples were matched on hospital, age, duration of subfertility, primary or secondary subfertility and diagnosis. Primary outcome was cumulative ongoing pregnancy rate after three years. Time to pregnancy was censored at the moment couples were lost to follow up or when their child wish ended and, for the no-treatment group, when couples re-started treatment. Results: After three years, there were 18 pregnancies in the stopped treatment group (25%) versus 41 pregnancies in the IUI group (28%) (RR 1.1 (0.59–2.2)( p = 0.4)). The cumulative pregnancy rate after three years was 40% in both groups, showing no difference in time to ongoing pregnancy (shared frailty model p = 0.86). Conclusions: In couples with unexplained subfertility and a poor prognosis for natural conception, treatment with IUI does not to add to expectant management. There is need for a randomized clinical trial comparing IUI with expectant management in these couples.